Experimental Analysis of Sugarcane Bagasse Ash Behavior as a Partial Replacement for Cement in Concrete Mix - Khatun Amreen; Reddy V. Phaninder; Chandrashekar Rakesh; Sravanthi; Kumar Manish; Kumar C. Vivek (E3S Web of Conferences)
The expansion of the infrastructure industry has led to the production and use tons of cement. A significant amount of CO2 has been released throughout the cement-making process. A growing number of people are considering agriculture waste as a feasible substitute for conventional cementitious materials due to its high silica concentration and renewable nature. The waste-free renewable energy source known as sugarcane bagasse ash (SCBA) is produced from the fibres of sugarcane. In this experimental study SCBA as a partial replacement of cement has been utilized to test strength and durability of the concrete mix. In this experimental work sugarcane bagasse ash is partially replaced as 2.5%, 5.0%, 7.5%, 10.0%, 12.5%. 15.0% and 20.0% with cement in concrete mix. The experimental results concluded that compressive strength increased when 10% SCBA was substituted, and split tensile strength maximum strength increased somewhat after that. The results of the investigation support the notion that the concrete used in construction has excellent durability when partially replaced with (SCBA). Additionally, the flexural behavior performed exceptionally well when replaced with 10% bagasse ash. Owing to its microparticle size and crystallographic character, bagasse ash exhibits increased performance when used as a supplementary material. The study concluded overall performance is achieved by replacing 10% of the SCBA in treated concrete.